Strategi peningkatan jumlah penyewaan di Audiovisual.id dengan metode SWOT dan Marketing Mix 7P - Yoseph, Jemima Davini; Hadisantono; Hanandoko, Theodorus B.; Dewa, Parama Kartika (Universitas Atma Jaya Yogyakarta, 2025)
Audiovisual.id is a subsidiary of PT Jawara Kreasitama which focuses on audio visual equipment rental. Audiovisual.id, which is located in Yogyakarta, will experience a decrease in rentals in 2023 by 35.54%. Based on observations made by interviewing stakeholders, problem mapping was carried out and the root of the problem was obtained by going through an elimination process using the Einsenhower Matrix, namely limited marketing reach. The root of the problem needs to be resolved so that there will be an increase in rentals in the business. The root of the problem of limited marketing reach is resolved with a growth strategy (S-O). The method used is Strength, Weakness, Opportunity and Threat (SWOT) with the help of the Marketing Mix 7P marketing mix. The tool used to determine the assessment of Audiovisual.id services and consumer expectations is with a questionnaire. The survey results show that it is necessary to provide a loyalty program or sustainability collaboration with event organizers, schools, universities and other institutions. Collaboration was successfully carried out with 5 vendors in Yogyakarta. The results of this collaboration can add 5 rental interactions which will continue every year. The agreed collaboration can show that by expanding the reach and establishing one of the vendors as a regular customer, it will result in several additional rental transactions and increase the number of rentals.